Le para-musée et les spectres de l’infrastructure - Sternfeld, Nora (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2026)
In an elegant display case at a Museum of Modern Art (MoMA) exhibition in New York, archival documents from the Art Workers’ Coalition and its 1969 actions at the museum recount struggles for artists’ rights and raise questions of political and social justice. The material is carefully preserved and formally presented. Yet how should we interpret the Coalition’s thirteen demands to MoMA—demands such as free admission, a dedicated section for the work of Black artists, and a public hearing on “The Museum’s Relationship to Artists and Society”? The display case protects what it contains while highlighting the value of these documents. But what does it mean for political demands addressed to the museum itself to appear inside the museum’s vitrines? In this text, Nora Sternfeld examines these concrete questions alongside broader ones: What does the relationship between institutions and anti- institutional struggles look like from the institution’s own perspective? If a museum’s responsibility toward its collections involves what she calls critical fidelity, then how might an institution remain faithful to the materials it preserves? Is it simply a matter of protecting the sheet of paper on which the thirteen demands were typed, or does fidelity require acting in accordance with what that document advocates? Shouldn’t an institution that wishes to be faithful to its objects also be faithful to the demands those objects articulate—in this case, by implementing them? And if we want to imagine forms of progressive conservation, how might museums preserve the conflicts embedded within their objects and documents so that these tensions can be reactivated, rather than neutralized or paralyzed by institutional practices?